Abortion legalization and adolescent fertility: new evidence for Uruguay based on the synthetic control method - Velázquez Battistessa, Cecilia (2024)
Following abortion legalization in Uruguay in late 2012, adolescent fertility rate fell by more than half. This paper aims at establishing a causality relationship. To estimate the impact of the abortion reform on adolescent fertility I use the Synthetic Control Method by comparing trends of Uruguay with Latin America and the Caribbean countries with restrictive abortion laws. Results suggest adolescent fertility rate was reduced in the postreform period by an average of 8.3 births per 1,000 girls aged 15-19, a decline of almost 15% with respect to the synthetic control unit. In-space placebos indicate this effect is statistically significant at the 5% level. This conclusion holds after conducting an in-time placebo test and a leave-one-out test. To the present time, evidence on the impact of Uruguayan abortion legalization on adolescent fertility that has addressed endogeneity is mixed, and based entirely on identification strategies that exploit different sources of exogenous within-country variation that determines the exposure to the reform. My contribution here is to exploit between-country variation, bringing new evidence to the on-going debate.